2006
DOI: 10.1080/02770900600709781
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Home Triggers for Asthma: The Latino Community Health Worker Approach

Abstract: This study assessed the ability of a community health worker asthma intervention to change home asthma triggers. A total of 56 children and 47 adults with asthma were enrolled. Home trigger scores for the children averaged 2.8 at the initial home visit and then 2.3, 2.1, and 2.0 at 3, 6, and 12 months. Home trigger scores for the adults showed a similar trend. Every home visit was associated with a 0.32 reduction in home trigger score (p < 0.01) for children and a 0.41 reduction (p < 0.01) for adults. This int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…We also experienced excellent retention with the three-month (95% for the in-person interviews) and six-month (89% for the phone interviews) follow-up periods. This bolsters existing asthma research focusing on Latino caregiver education that has shown how home-based and school-based parental instruction by community educators can enhance knowledge acquisition and improve asthma outcomes [39][40][41]. These educational interventions involved one-on-one coaching with caregivers across a scheduling spectrum.…”
Section: Discussionmentioning
confidence: 77%
“…We also experienced excellent retention with the three-month (95% for the in-person interviews) and six-month (89% for the phone interviews) follow-up periods. This bolsters existing asthma research focusing on Latino caregiver education that has shown how home-based and school-based parental instruction by community educators can enhance knowledge acquisition and improve asthma outcomes [39][40][41]. These educational interventions involved one-on-one coaching with caregivers across a scheduling spectrum.…”
Section: Discussionmentioning
confidence: 77%
“…Fewer emergency department visits were observed as well, but the difference was not significant. A study by Martin et al 11 also…”
Section: Discussionmentioning
confidence: 98%
“…Research interventions that test the efficacy of self-management interventions may wish to explore the added value of community level interventions that involve the entire family on asthma outcomes. [34]. Another potential research area is a comparison of the impact of a shared asthma action plan between adult patients and close family members versus a traditional asthma action plan focusing on the patient only.…”
Section: Discussionmentioning
confidence: 99%